Anteseden Niat Beli Ulang Belanja Online: Uji E-kepuasan Sebagai Mediasi - Jeanne Ellyawati; Agnes Pepethinganing Piwi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Purpose This study aims to predict the effect of security, trustworthiness, ease-of-use, and privacy concerns on repurchase-intentions and the role of e-satisfaction as a mediator.Methodology Data were collected through structured questionnaires. We used a cross-sectional online survey, with purposive and snowball sampling methods. SmartPLS was employed to verify the hypothesis.Findings Security, trust, ease-of-use, and privacy issues have a positive effect on e-satisfaction and repurchase intentions. E-satisfaction partially mediates the effect of the four antecedent variables on repurchase-intention.Originality/Novelty This study focuses on consumers' online shopping experience as measured by security, trustworthiness, ease-of-use, and privacy concerns to predict e-satisfaction and repurchase intention. The research setting was conducted in the three largest marketplaces in Indonesia with heterogeneous research subjects. The results show that ease-of-use is the most dominant predictor of influence on e-satisfaction and repurchase intention.Implications Companies are suggested to always provide online shopping applications that are easy to understand, access, and operate by consumers. Besides, security in transactions is very important so that consumer privacy is maintained and can strengthen consumer trust. These efforts focus on satisfying consumers first because consumers who experience e-satisfaction will be more likely to purchases on the same marketplace.